Cost-Benefit Analysis of Financial Legislation Changes in Kosovo: A Comparative Legal and Economic Approach - Morina, Fitore; Nuhiu, Artor; Peci, Bedri; Beshi, Simeana; Gashi, Fitim; Kozhani, Egzona (PRAWO i WIĘŹ, 2025)
This research provides a legal and empirical examination of changes to Kosovo’s financial legislation utilizing a cost-benefit framework. Focusing on the consequences of legal reforms to VAT Law, CIT Law and banking regulations, it considers these changes from a broader macroeconomic and institutional perspective. Kosovo’s ongoing process of integration and harmonization with the European Union (EU) financial legislation necessitates addressing the issue of how these new legislative changes will impact its national development in terms of social and economic effects. The originality of the research lies in the application of mixed methodology that incorporates quantitative economic analysis with a comparative legal analysis of the benefits and costs of legislative changes. Despite the research context being at a national level, it presents valuable information that can help inform better alignment with the EU directives. The analysis sill be useful for policymakers and stakeholders in Kosovo as well as in other developing countries dealing with similar legislative changes. The findings provide evidence-based analysis of financial legislation reforms that may meaningfully impact large-scale and long-term policy initiatives framed in the context of ongoing sustainable economic development.